Para powerlifting performance: A systematic review - Oliveira, J. I. V.; de Lucena, E. G. P.; Ferland, P.-M.; Oliveira, S. F. M.; Uchida, M. C. (International Journal of Sports Medicine, 2023)
This research aimed to conduct a systematic review of para powerlifting strength performance. The searches were conducted in three electronic databases: PubMed, Scopus, and SPORTDiscus. Intervention studies related to para powerlifting performance were included. The main information was extracted systematically, based on criteria established by the authors. The data on study design, sample size, participant`s characteristics (e. g. type of disability, sex, age, body weight, and height), training experience, assessment tools, physical performance criteria, and force-related outcomes were extracted and analyzed. The studies (n=9) describe factors related to biomechanics and performance. Outcomes revealed that the one-repetition maximum test is used as load prescription and that para powerlifting should work at high speeds and higher loads. Regarding technique, grip width with 1.5 biacromial distance provides a good lift and partial amplitude training as an alternative to training. There are no differences in total load and movement quality in the lumbar arched technique compared with the flat technique. As a monitoring method, repetitions in reserve scale was used for submaximal loads. Finally, our outcomes and discussion indicated strategies and techniques that can be used by para powerlifting coaches.